2016
DOI: 10.2967/jnumed.116.179648
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between SUVmax and CT Radiomic Analysis Using Lymph Node Density in PET/CT-Based Lymph Node Staging

Abstract: In patients with lung cancer (LC), malignant melanoma (MM), gastroenteropancreatic neuroendocrine tumors (GEP NETs), and prostate cancer (PCA), lymph node (LN) staging is often performed by 18 F-FDG PET/CT (LC and MM), 68 Ga-DOTATOC PET/CT (GEP NET), and 68 Ga-labeled prostate-specific membrane antigen PET/CT (PCA) but is sometimes not accurate because of indeterminate PET findings. To better evaluate malignant LN infiltration, additional surrogate parameters, especially in cases with indeterminate PET findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 29 publications
3
32
1
Order By: Relevance
“…18 F-FDG-PET/CT: 18 F-FDG-PET/CT examinations were performed as part of preoperative staging according to clinical routine using a Biograph 6 PET/CT Scanner (Siemens, Erlangen, Germany). Imaging sequences and protocols were described earlier in detail (20,21): after fasting for at least 6 hours (blood glucose level below 150 mg/dl), 4 MBq/kg body weight of 18 F-FDG were administered intravenously 60±5 minutes before the FDG-PET/CT scan. The following examination protocols and reconstruction parameters were applied: slice thickness/reconstruction increment of 5.0/2.5 mm, standard soft-tissue reconstruction kernel B30 and B70 high-resolution.…”
Section: Methodsmentioning
confidence: 99%
“…18 F-FDG-PET/CT: 18 F-FDG-PET/CT examinations were performed as part of preoperative staging according to clinical routine using a Biograph 6 PET/CT Scanner (Siemens, Erlangen, Germany). Imaging sequences and protocols were described earlier in detail (20,21): after fasting for at least 6 hours (blood glucose level below 150 mg/dl), 4 MBq/kg body weight of 18 F-FDG were administered intravenously 60±5 minutes before the FDG-PET/CT scan. The following examination protocols and reconstruction parameters were applied: slice thickness/reconstruction increment of 5.0/2.5 mm, standard soft-tissue reconstruction kernel B30 and B70 high-resolution.…”
Section: Methodsmentioning
confidence: 99%
“…In one study, PET, CT, and PET/CT features were used to predicting local tumor control in head and neck cancer [129] by multivariate cox regression with a confidence interval (CI) CI CT and CI PET/CT of 0.73, however, CT-based radiomics overestimated the probability of tumor control in the poor prognostic groups. Another study found a correlation of PET and CT features using lymph node density [176] and concluded that CT density measurements together with PET uptake analysis increases the differentiation between malignant and benign LN. Disease-free survival prediction in non-small cell lung cancer patients can be performed in PET/CT images with an area under the receiver operator characteristic curve (AUC) of 0.68 when employing combined PET/CT features [177].…”
Section: Radiomicsmentioning
confidence: 99%
“…This might be due to the lower resolution and contrast of nuclear medicine images. 33 In the study by Giesel et al, 41 only LNs were evaluated in order to discriminate those with metastatic infiltration from benign ones. Despite the good results reported, the robustness of radiomic features extracted from small volumes of LNs was overlooked.…”
Section: Discussionmentioning
confidence: 99%